2019
DOI: 10.1002/acm2.12704
|View full text |Cite
|
Sign up to set email alerts
|

Fixed‐jaw technique to improve IMRT plan quality for the treatment of cervical and upper thoracic esophageal cancer

Abstract: The purpose of this study was to investigate the potential advantages of the fixed‐jaw technique (FJT) over the conventional split‐field technique (SFT) for cervical and upper thoracic esophageal cancer (EC) patients treated with intensity‐modulated radiotherapy. The SFT and FJT plans were generated for 15 patients with cervical and upper thoracic EC. Dosimetric parameters and delivery efficiency were compared. An area ratio (AR) of the jaw opening to multileaf collimator (MLC) aperture weighted by the number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…The results showed that the dosimetric parameters of the FJ IMRT technique could meet the clinical requirements like the other three techniques; the D 2 , D 98 , conformity and homogeneity for the PTV-G and PTV-C with the FJ IMRT plan were not significantly different from those of the JT IMRT and SJ IMRT plans, and this was consistent with the study from Wang et al [ 16 ] and Song et al [ 18 ]. The results of this study also showed that the TCP of the FJ IMRT plan was similar to that of the JT IMRT, SJ IMRT and JT VMAT plans, and the absolute differences were small.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results showed that the dosimetric parameters of the FJ IMRT technique could meet the clinical requirements like the other three techniques; the D 2 , D 98 , conformity and homogeneity for the PTV-G and PTV-C with the FJ IMRT plan were not significantly different from those of the JT IMRT and SJ IMRT plans, and this was consistent with the study from Wang et al [ 16 ] and Song et al [ 18 ]. The results of this study also showed that the TCP of the FJ IMRT plan was similar to that of the JT IMRT, SJ IMRT and JT VMAT plans, and the absolute differences were small.…”
Section: Discussionsupporting
confidence: 88%
“…Fixed-jaw IMRT has also been indicated in breast cancer to effectively reduce the low dose to normal tissues while maintaining target coverage [ 17 ]. Song et al also showed the advantages of improving the quality of the IMRT plan with the use of the fixed-jaw technique for cervical and upper thoracic esophageal cancer [ 18 ].…”
Section: Introductionmentioning
confidence: 99%